2002
DOI: 10.1159/000048651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rivastigmine on Cognitive Function in Dementia with Lewy Bodies: A Randomised Placebo-Controlled International Study Using the Cognitive Drug Research Computerised Assessment System

Abstract: This study was designed to assess the effects of rivastigmine (Exelon®) on the cognitive functioning of patients suffering from dementia with Lewy bodies. This was a prospective, multi-centre, randomised, double-blind, placebo-controlled exploratory study conducted at sites in the UK, Spain and Italy. The treatment period was 20 weeks with a 3-week posttreatment follow-up. The primary outcome measures were the Cognitive Drug Research (CDR) computerised assessment system and the Neuropsychiatric Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(141 citation statements)
references
References 28 publications
6
133
1
1
Order By: Relevance
“…2B). According to earlier reports regarding the degradation of Hup A (metabolized via CYP1A2), Don (metabolized via CYP2D6), and Riv (Matsui et al, 1999;Wesnes et al, 2002;Ma et al, 2003a), these AChEIs should not interfere with CYP2E1 activity in mouse liver microsomes. Taken together, these data indicated that AChEI-induced hepatic protection was not accomplished by affecting GSH content and CYP2E1 activity, suggesting that this effect was not related to the production of NAPQI.…”
Section: Downloaded Frommentioning
confidence: 93%
“…2B). According to earlier reports regarding the degradation of Hup A (metabolized via CYP1A2), Don (metabolized via CYP2D6), and Riv (Matsui et al, 1999;Wesnes et al, 2002;Ma et al, 2003a), these AChEIs should not interfere with CYP2E1 activity in mouse liver microsomes. Taken together, these data indicated that AChEI-induced hepatic protection was not accomplished by affecting GSH content and CYP2E1 activity, suggesting that this effect was not related to the production of NAPQI.…”
Section: Downloaded Frommentioning
confidence: 93%
“…Attention was measured using the Cognitive Drug Research computerized battery. 16 Mean response times of simple reaction time, choice reaction time, and digit vigilance were summed to produce a Power of Attention score. 16 Digit vigilance accuracy was also evaluated as part of this domain.…”
Section: Participants Between June 2009 and Decembermentioning
confidence: 99%
“…16 Mean response times of simple reaction time, choice reaction time, and digit vigilance were summed to produce a Power of Attention score. 16 Digit vigilance accuracy was also evaluated as part of this domain. Memory was assessed with Pattern Recognition Memory (PRM), Spatial Recognition Memory (SRM), and Paired Associates Learning (PAL) from the computerized Cambridge Neuropsychological Test Automated Battery (CANTAB) battery.…”
Section: Participants Between June 2009 and Decembermentioning
confidence: 99%
“…The CDR system has a strong factor structure that has been demonstrated in both healthy and diseased populations (Wesnes et al, 2000(Wesnes et al, , 2002. The individual test scores from the battery load strongly onto four global outcome factors (Quality of memory; Speed of attention; Accuracy of attention; Speed of memory) and two sub-factors (Working memory; Secondary memory).…”
Section: Primary Cognitive Outcome Measuresmentioning
confidence: 99%